Hydration of nucleic acids and nucleotides in aqueous ethanolic solutions determined by ultrasonic method - JUSZKIEWICZ, Adam (Archives of Acoustics, 1986)
Hydration numbers of mono-and disodium salts of nucleotides as well as of sodium and potassium salts of DNA and RNA were determined from ultrasonic velocity measurements. For comparative purposes hydration numbers of monosodium and monopotassium phosphates were also determined.